Asymmetric bioreduction of p-haloacetophenones by Mucor. (December 2013) - Zhang, Zuohui; Liu, Xiongmin; Ma, Li; Zhuo, Meifang; Shen, Fang
Abstract A number of p-haloacetophenones were asymmetrically bioreduced to their corresponding (S)-alcohols by Mucor sp. CG10 with good conversion and excellent enantioselectivity. The results showed that the electronic effects of the halogen substituent (X-group) affected the conversion of the substrates and the enantioselectivity of the reaction. The trend observed was as the X-group at the para-position became more electron donating from F, to Cl, Br and I, the conversion of substrates decreased, while the enantioselectivity increased.